Perlindungan Hak Anak Pelaku Pembunuhan Dalam Masa Pembinaan Di Lembaga Pembinaan Khusus Anak Kelas II Bandung - Syakirah, Gina El; Susilowati, Ellya; Rosilawati, Rosilawati (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2025)
Children Who Commit Homicide as Part of Children in Conflict with the Law (CICL) have Equal Rights to Protection when undergoing rehabilitation sentences at the Special Child Development Institution (LPKA). This study aims to describe the protection of children's rights at LPKA Class II Bandung using a descriptive qualitative approach. The research focuses on the rights to health care and treatment, education, skills training, and social services. Informants consisted of two juvenile inmates and four LPKA staff members. Data were collected through interviews, observations, and documentation. The findings indicate that LPKA has made efforts to fulfill children's rights in accordance with regulations; however, challenges remain, particularly in the provision of social services, especially psychosocial support to address the trauma still experienced by children who have committed homicide. This study recommends strengthening the role of staff or child guardians, particularly in providing psychosocial assistance, as part of fulfilling the rights of children requiring special protection. Keywords: Protection; Child Offender of Homicide; LPKA (Special Child Development Institution); Child Rights